Oral Cancer Examinations Among Adults at High Risk: Findings from the 1998 National Health Interview Survey - Mark D. Macek, DDS, DrPH; Britt C. Reid, DDS, PhD; Janet A. Yellowitz (Blackwell Synergy, 2003)
Cigarette smoking and alcohol use are risk factors for oral and pharyngeal cancer. Recommendations for periodic oral cancer examinations highlight the importance of examining high-risk smokers and alcuhol users. This investigation assessed whether cigarette smoking and alcohol use were associated with receipt of an oral cancer examination